Serum ferritin in Yemeni patients with sickle cell anemia: Association with sociodemographic factors and hematological profiles - Abdulsalam Al-Shami; Lutfi A. S. Al-Maktari; Lina Qasem; Khalid Aldhorae; Shimaa AL-Khaship (PLoS ONE, 2026)
Background Iron overload remains a critical complication secondary to transfusional therapy and altered iron metabolism in patients with sickle cell anemia (SCA). Hyperferritinemia often serves as a surrogate marker for iron overload; however, as an acute-phase reactant, it may be elevated due to chronic inflammation, infection, or liver disease, potentially overestimating true iron stores. In Yemen, the burden of SCA is high, yet local data on the frequency of hyperferritinemia are scarce. This study aimed to describe the distribution of serum ferritin (SF) levels and the proportion of SCA patients with hyperferritinemia among adolescents and young adults attending the YSTH clinic in Sana’a, and to explore associations with hematological, and sociodemographic parameters. Methods A prospective cross-sectional study was conducted between June and December 2024, involving 80 participants (aged ≥ 15 years). The data were analyzed using SPSS version 26. Due to the non-normal distribution and high dispersion of SF, the Median (IQR) and Spearman correlation were utilized. Bivariate analysis calculated crude odds ratio at (95% CI) to identify predictor of elevated SF. Statistical power was limited by the sample size ( N = 80) to detect weak associations. Results The study enrolled 80 SCA patients with a mean (±SD) age of 18.5 (±3.69) years, of whom 65% were males and 35% were females. The median (IQR) SF level was 1645 ng/mL (414–3525), with values ranging from 77.1 to 4500.0 ng/mL. Approximately 85% of patients exhibited elevated SF level (≥300 ng/mL). While red cell indices did not significantly predict the risk of hyperferritinemia, a significant positive correlation was observed between SF levels and white blood cell count ( p = 0.03), suggesting a possible link with the inflammatory state. No significant associations were found between sociodemographic factors and high SF levels. Conclusion A high prevalence (85%) of hyperferritinemia ( ≥ 300 ng/mL) was observed among SCA patients attending the YSTH in Sana’a, Yemen, suggesting probable iron overload. While findings support routine SF screening but highlight the need for future studies incorporating inflammatory markers (e.g., CRP) and systematic transfusion histories to definitively quantify the iron overload burden in this population.